2018
DOI: 10.1111/opec.12134
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between electricity consumption, trade openness and economic growth in India

Abstract: The present study explores the empirical relationship between electricity consumption, trade openness and economic growth in India utilising cointegration tests and Granger causality vector error correction model for the period 1971–2016. The results of ARDL model reveal that the variables are cointegrated. The robustness of the long‐run relationship between variables is confirmed by applying Hatemi‐J cointegration model. The empirical results show that electricity consumption statistically significantly stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
8
1
1
Order By: Relevance
“…Energy has been recognised as the lubricant for sustainable economic development (Ohlan, 2018), and access to energy is essential for achieving industrialisation in any economy. Energy commodities foster economic development by improving the country's level of productivity, income and employment generation (Akinwale and Muzindutsi, 2019;Nasreen and Anwar, 2014).…”
Section: Energy Consumption International Trade and Economic Growth Situation Of Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Energy has been recognised as the lubricant for sustainable economic development (Ohlan, 2018), and access to energy is essential for achieving industrialisation in any economy. Energy commodities foster economic development by improving the country's level of productivity, income and employment generation (Akinwale and Muzindutsi, 2019;Nasreen and Anwar, 2014).…”
Section: Energy Consumption International Trade and Economic Growth Situation Of Nigeriamentioning
confidence: 99%
“…International trade motivates economic activities which call for more energy usage (Kyophilavong et al, 2015). Most of the emerging economies are transiting from agricultural-based sector towards industrial sector which further requires additional energy demand, though newly imported technologies which could cause low-energy intensity is also possible through trade openness (Ohlan, 2018). Energy is considered as an essential factor in the production and distribution of goods.…”
Section: Introductionmentioning
confidence: 99%
“…Studi empiris mengenai kausalitas konsumsi listrik dan pertumbuhan ekonomi banyak dilakukan di Eropa, Asia, Amerikan latin dan Afrika, seperti, Ohlan (2018) for India; Cheng Lu (2016) Soytas and Sari (2003) for Argentina, Turkey, Korea, France, Italy, West Germany, and Japan.…”
Section: Pendahuluanunclassified
“…A study by Li et al (2017) for emerging economies and found OFDI as the main driver of growth. Ohlan (2018) explored the positive association of energy use and grwoth. Dwumfour and Ntow-Gyamfi (2018) exposed the positive relationship between economic development and NR.…”
Section: Impact Of Ofdi Nr To Fd and Re On Economic Developmentmentioning
confidence: 99%